CONSUMER SOCIETY, COMMODIFICATION OF CHILDHOOD AND CURRENT CHALLENGES FOR EDUCATION - Renato de, Oliveira Brito; Aico Sipriano, Nogueira (Journal of Human Capital Development (JHCD), 2012)
This paper discusses the current challenges facing education, given the growing process of commodification of childhood by consumer society. From the presentation of key concepts such as alienation, competition, consumption and new electronic media, elements that shape social relations of contemporary society, the paper first discusses the process of social reification as a phenomenon leading to the creation of a society dominated by production and distribution of goods. Secondly the analysis focuses on the school as an important locus of production and reproduction of market forces and the constant process of transformation of education into a commodity. The new media are then analyzed as essential tools in this new phase of development of productive forces, with discussion of alternatives for confronting this phenomenon by the school, among which the need for ongoing investment in the critical and reflective skills of the students stands out, seen as the only effective instrument against the process of alienation. The article then analyzes the need for professionals in the school environment who are qualified to develop this work, as well as the importance of integration of the whole school community in a political pedagogical project for this purpose. KEYWORDS: political pedagogical project, commodification of childhood